Evaluation of neighborhood impacts caused by companies of the high-tech industrial cluster of São Carlos, SP, Brazil - de Lollo, Josẽ A. [UNESP]; Röhm, Sergio Antonio; Martinetti, Thais H. (Journal of Urban and Environmental Engineering, 2008)
The purpose of this study was to develop a methodology for evaluating neighborhood impacts using a Geographic Information System (GIS) and to apply the procedures to the companies of the High-Technology Industrial Cluster of São Carlos. To this end, an evaluation was made of the neighborhood impacts on the physical environment, urban components, quality of life, and urban infrastructure using impact matrices, and the impacts were assigned scores according to type, order, magnitude and duration. Fifty one companies were examined based on data provided by the companies themselves and on field surveys. The impacts are represented spatially in proportional symbols maps, based on the spatial distribution of the companies in the urban area of the city of São Carlos and the areas of influence of each company. The application of the proposed methodology served to validate it and indicated that the neighborhood impacts caused by the companies of this study are related to each company's type of activity, its size, and its occupation of the area. © 2008 Journal of Urban and Environmental Engineering (JUEE). All rights reserved.
Keywords: High-tech cluster; Industry impacts; Law 10257/01; Neighborhood impacts; Urban planning